2016
DOI: 10.1016/j.rmed.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to accessing primary care resulting in hospital presentation for exacerbation of asthma or chronic obstructive pulmonary disease in a large teaching hospital in London

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) account direct costs of £1 billion each per year in the United Kingdom (UK). A national review of asthma deaths found that a significant proportion of patients die without seeking medical assistance or before emergency medical care could be provided. This study aims to establish the pathway that patients undertake to access care in the lead up to an accident and emergency (A&E) attendance and/or inpatient admission. Patients attending A&E and/or following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Some studies have found the presence of consistently poor reporting behaviours among COPD patients, resulting in most exacerbations being unreported [55,56], while other work has highlighted that 50% of asthma and COPD patients were found not to receive GP intervention prior to presenting to hospital [57]. Therefore, early detection of exacerbations and prompt intervention is preferred as they have been shown to reduce recovery time, improve health-related quality of life and reduce the risk of hospitalisation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found the presence of consistently poor reporting behaviours among COPD patients, resulting in most exacerbations being unreported [55,56], while other work has highlighted that 50% of asthma and COPD patients were found not to receive GP intervention prior to presenting to hospital [57]. Therefore, early detection of exacerbations and prompt intervention is preferred as they have been shown to reduce recovery time, improve health-related quality of life and reduce the risk of hospitalisation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown COPD patients demonstrate consistently poor reporting of exacerbations, with 50% of patients failing to seek GP treatment before hospitalisation. [93][94][95] The potential for DHI to increase the disease knowledge of COPD patients is a promising area for future research, as it presents an opportunity to improve patient safety and reduce healthcare utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they don´t have more frequent readmissions during the follow-up period. In the literature, asthma exacerbations requiring hospital admission are usually a minority, since most patients are discharged from the Emergency Room [14,65].…”
Section: Discussionmentioning
confidence: 99%